The Permeating Effects of Violence on Health Services and Health in Mexico - Vargas, Laura (Journal of interpersonal violence, 2022)
Mexico?s violence related to organized crime activity has grown to epidemic levels in the last 12 years. We interviewed 22 Mexican health care providers from five states to examine how violence impacts health care services and health. We transcribed and analyzed semi-structured interviews using framework analysis. Our findings describe the ways in which community violence in Mexico permeates health care services, impacting health care providers, and the health of patients. We developed a model to reflect our main themes that illustrate how violence permeates health care services over geographic space and time. We identified three thematic categories: (a) the impact of violence on health care facilities and service provision, (b) the impact of violence on providers, and (c) the impact of violence on the health of the community. Our model articulates a dynamic process of the spread and permeation of violence. Prior literature focuses on the impact of violence as an occupational hazard and the effect of war or civil conflict on health care services. We extend this literature by documenting the impacts of widespread violence on Mexican health care services and providers. We discuss how violence impacts services, providers, and health in a country that is not officially at war. We compare our findings to previous literature on occupational violence in health professions and the impacts on health services in official war zones. Finally, we highlight the implications for health care practice and policy. We suggest that violence should be considered throughout the care continuum in Mexico and make the case for violence as a structural contributor to health and health disparities in Mexico. We suggest additional research on this under-investigated topic.